(untitled) (diségno, 2022)
The competition for the Palazzo di Giustizia in Rome takes place in four phases that develop between 1884 and 1887. The project of the third competition (1886-1887), drawn up by Ernesto Basile (Palermo 1857-1932), reveals a great maturity design that transforms the complex functional program into a rigorous neo-Renaissance style building. The jury recognizes the quality of the project and selects it for the final phase by invitation (1887) together with that one of Guglielmo Calderini, who will be the winner. The original drawings of the unrealized work are kept at the Basile Endowment of the Department of Architecture of the University of Palermo: among them there are sketches, preparatory drawings and final project drawings, mainly in pencil and ink on paper and cardboard, with, in some cases, monochrome watercolor glazes. The studio applies a consolidated methodology: analysis of the original drawings, survey, plane vectorization, graphic analysis of compositional functions and parties, interpretation of graphic inconsistencies, three-dimensional modeling, rendering and photo insertions. Thanks to an in situ photographic campaign it was possible to perform some photo insertions, processed respecting both the congruence of the perspective view of the photos and the lighting conditions. The photo insertions allow a visual comparison between the realized work and the unbuilt one, as well as the relationships established with the urban context.